Exogenous supplementation of N-acetylcysteine can reduce hepatotoxicity induced by ascites fluid (cell-free) adsorbed over Protein-A-containing Staphylococcus aureus Cowan-I without compromising its antitumor effect† - Ashish S Verma; Priyadarshini Mallick; Premendra D Dwivedi; Anchal Singh (Wolters Kluwer Medknow Publications, 2019)
Introduction: Hepatotoxicity along with enhanced mortality has remained a major concern during the development of antitumor therapy with the use of cell-free ascites fluid adsorbed (ad-AF) over Protein-A-containing Staphylococcus aureus Cowan I (SAC). Major issue with ad-AF inoculation is the significant depletion of hepatic glutathione (GSH). Exogenous supplementation of -SH contents to the host has offered an encouraging hope to explore the possibilities to use ad-AF as a therapeutic material due to its antitumor effects. GSH and l-cysteine have shown a promise with the recovery of -SH contents as well as the recovery of phase I and phase II biotransformation enzymes. Aforementioned observations prompted us to try other -SH donors. Materials and Methods: Therefore, in this study, N-acetylcysteine (NAC) was used as an exogenous source to provide -SH contents to reduce hepatotoxicity and mortality induced by ad-AF treatment. Results: Exogenous supplementation of NAC along with ad-AF treatment to ascites tumor bearers has shown a significant protection against hepatotoxicity and mortality caused by ad-AF. NAC substitution along with ad-AF has significantly enhanced the mean survival time (MST), without altering the antitumor effect of ad-AF as evident from tumor cell counts and viability. Discussion: NAC supplementation has been successful to recover hepatic -SH contents along with the significant recovery of phase I and phase II biotransformation enzymes. Marker enzymes for liver injury have also given clear-cut indications for the recovery of tumor bearers from hepatotoxicity induced by ad-AF. Conclusion: This study has shown that exogenous supplementation of NAC protects the host from the enhanced mortality and hepatotoxicity induced by ad-AF. These observations offer a hope to develop ad-AF as one of the probable treatment strategies for ascites tumors at least at experimental levels.